2023
DOI: 10.1002/agj2.21328
|View full text |Cite
|
Sign up to set email alerts
|

Ohio grain crop response to sulfur fertilization

Abstract: Continuous declines in atmospheric sulfur (S) deposition along with increased S removal rates with crop harvest has the potential to lead to S deficiency in Ohio field crops. As a result, S fertilization has become more common over the past decade.However, the extent of S deficiency is unknown, as inherent soil properties and management practices influence S availability and uptake. We conducted 96 replicated trials, from 2013 to 2021 to (1) examine the response of corn (Zea mays L.), soybean [Glycine max (L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Despite the decline in deposition from the air, however, not all areas and crops show a high frequency of response to sulfur application. An extensive set of field trials in Ohio from 2013 to 2021 showed less widespread response than expected (Fleuridor et al, 2023). Out of 96 trials, only seven responded positively: 4 out of 50 corn trials, 3 of 34 soybean trials, and none of 12 wheat trials.…”
Section: Recent Field Testingmentioning
confidence: 76%
“…Despite the decline in deposition from the air, however, not all areas and crops show a high frequency of response to sulfur application. An extensive set of field trials in Ohio from 2013 to 2021 showed less widespread response than expected (Fleuridor et al, 2023). Out of 96 trials, only seven responded positively: 4 out of 50 corn trials, 3 of 34 soybean trials, and none of 12 wheat trials.…”
Section: Recent Field Testingmentioning
confidence: 76%
“…Therefore, it is assumed that SO 4 2− concentration in soil was adequate for potato development; thus, the S rates applied to the plots did not influence plant biomass responses. However, in grain crops, the soil S concentration had a weak relationship with yield compared to the leaf S concentration as the S deficiency indicator (Fleuridor et al., 2023; Kaur et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Crop S uptake varies with legacy S concentration in soil (Kim et al., 2013), similar to the findings in this study, where the soil with high initial S concentration was less responsive to fertilization, regardless of S source. It was also reported that applying the S fertilizer increases the S concentration in the grains and plant tissue; however, it does not necessarily positively impact crop yield (Carciochi et al., 2019; Fleuridor et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, this scarcity was attributed to the widespread perception of an abundant natural supply, as indicated by the absence of positive responses to S additions (Dick et al, 2008). However, cases of crop S deficiencies have started to multiply in several parts of the world in the last two decades, which has led to an increasing demand among farmers for S testing methods (Goyal et al, 2021;Kovar & Grant, 2011;Mahal et al, 2022; see also Fleuridor et al, 2023). Reduced atmospheric deposition of anthropogenic S, increasing use of N and P fertilizers without S impurities, soil impoverishment, and increased crop demand and export of S have been identified as the main causes of this change in trend (Scherer, 2009;Webb et al, 2016).…”
Section: Introductionmentioning
confidence: 99%